Ecosystems for Entrepreneurship: A Study of Supportive Environments and Their Impact - Yana Ermawati (Amkop Management Accounting Review (AMAR), 2023)
This study explores the impact of supportive environments, or entrepreneurial ecosystems, on the success and development of entrepreneurial activities across diverse geographic regions. Employing a qualitative approach, this research utilizes semi-structured interviews, focus groups, and document analysis to gather comprehensive insights from entrepreneurs, policymakers, investors, and educational institution representatives. The study focuses on various entrepreneurial ecosystems, examining the interactions between financial resources, government policies, educational institutions, cultural attitudes, and social networks. The findings underscore the critical role of financial resources, such as venture capital and angel investors, in fostering entrepreneurial success. Government policies that promote business-friendly regulations, tax incentives, and support for research and development significantly enhance entrepreneurial environments. Educational institutions provide essential knowledge, skills, and training as hubs for innovation. Positive cultural attitudes towards entrepreneurship and robust social networks also play pivotal roles in supporting entrepreneurial activities. The study highlights geographic disparities in resource distribution and entrepreneurial ecosystems' dynamic, evolving nature, emphasizing the need for tailored support mechanisms in developing regions. The study provides practical insights for startup founders, managers, and policymakers. It emphasizes the importance of fostering a culture of innovation, investing in R&D, and adopting agile methodologies. Policymakers can support startups by creating conducive regulatory environments and facilitating access to funding. Future research should explore the dynamic nature of innovation over time and across different industry contexts to further understand the mechanisms driving startup success.